Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Routledge, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". – Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Coming Out of the Castle: Gothic, Sexuality and the Limits of Language - Grove, Allen W. (Historical Reflections / Réflexions Historiques, 2000)
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; histoire; histoire et politique; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; thématiques; études littéraires

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme

Histoire de l'homosexualité en Europe: Berlin, Londres, Paris, 1919-1939 - Tamagne, Florence (Editions du Seuil, 2000)
Pour l'histoire de l'homosexualité en Europe, l'entre-deux-guerres représente une période cruciale. Comme jamais auparavant, l'homosexualité s'y manifeste au grand jour. Alors que l'Allemagne voit se constituer de véritables mouvements porteurs de revendications politiques qui font de Berlin la capitale de la nouvelle culture, l'Angleterre emprunte le chemin de la subversion de l'ordre victorien, que tandis que la France, malgré une plus grande tolérance, reste sensible à une homosexualité non militante et individualiste. Cette explosion libératrice des mœurs et des mentalités n'aura pourtant pas les retombées sociales et politiques espérées et c'est d'Allemagne que viendra, dans les années trente, le signal de la répression. Celle-ci frappera provisoirement d'un coup d'arrêt une dynamique qui reprendra soufflé dans les années soixante. Reste qu'en quelques années l'homoérotisme trouve une nouvelle légitimation, l'homosexuel devient une figure possible de l'existence sociale. C'est dire l'importance du livre de Florence Tamagne pour comprendre la lente et difficile marche vers la reconnaissance de la communauté homosexuelle et lesbienne.
Section: 691 p. ; 21 cm.
Keywords: 1900-1999; 1920-1929; 1930-1939; LGBTQIA2+; allemagne; angleterre; approches et analyses; berlin; cours; discipline; europe; france; histoire et politique; identités LGBTQIA2+; londres; militance; paris; premier cycle; périodes historiques; queer; régions géographiques; shm4000; thématiques